Education on the Utilization of Lerak (Sapindus Rarak DC) as an Environmentally Friendly Detergent Alternative for Chemistry Teaching Materials: Edukasi Pemanfaatan Lerak (Sapindus Rarak DC) menjadi Detergen Ramah Lingkungan sebagai Alternatif Bahan Ajar Kimia - A. Mutmainnah Taslim; Ayu Indayanti Ismail; Meili Yanti (Beru'-beru': Jurnal Pengabdian kepada Masyarakat, 2024)
The use of detergent is currently very widespread due to their effectiveness in removing stains compared to reguler soap. However, there are often overlooked environmental impacts associated with the use of these detergents. The environmental damage caused by detergents is a challenge in human life. Therefore, it is essential to transition to using more environmentally friendly alternatives. This initiative focuses on educating the use of Lerak (soapberry) as a natural alternative to chemical detergents. Lerak, also known as soapnut or soapberry, is the fruit of the Sapindus tree, which has long been used as a natural cleaning agent. Lerak contains saponins, a natural substance that produces foam and has cleaning properties. The components of Lerak are similar to those found in commercial soap and can help mitigate environmental damage.